2010
DOI: 10.1039/c001499k
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nitride as a versatile growth substrate for microspectroscopic imaging and mapping of individual cells

Abstract: Herein is described a general sampling protocol that includes culture, differentiation and fixing of cells in their preferred morphology on the one sample substrate (Si(3)N(4)) to enable subsequent diverse modern microspectroscopic analyses. The protocol enables unprecedented correlated and complementary information on the intracellular biochemistry of metabolic processes, diseases and their treatment, which offers the opportunity to revolutionize our understanding of cell and tissue biology at a molecular lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 34 publications
3
70
0
Order By: Relevance
“…This study also demonstrated that the spectroscopic features reported in this paper are also observed in FTIR spectroscopic images collected in transmission mode from thin sections mounted on Si 3 N 4 windows (see the Supporting Information), which do not suffer from this artifact and also have the advantage of being able to be used with a large range of microscopies and microspectroscopies. 53 Data Analyses. FTIR spectroscopic data were processed (normalized to the area of the amide I band at 1690−1610 cm −1 ) and functional group images were generated using Cytospec software (Cytospec, version 1.2.04).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This study also demonstrated that the spectroscopic features reported in this paper are also observed in FTIR spectroscopic images collected in transmission mode from thin sections mounted on Si 3 N 4 windows (see the Supporting Information), which do not suffer from this artifact and also have the advantage of being able to be used with a large range of microscopies and microspectroscopies. 53 Data Analyses. FTIR spectroscopic data were processed (normalized to the area of the amide I band at 1690−1610 cm −1 ) and functional group images were generated using Cytospec software (Cytospec, version 1.2.04).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The sample environment and window material need to be chosen deliberately to be x-ray compatible (resistant to the radiation and avoiding a strong background signal) and suited for cell culture. Silicon nitride (Si 3 N 4 ) membranes have proven to be an excellent growth substrate as well as window material [16].…”
mentioning
confidence: 99%
“…Historically, different substrates, ranging from thin polycarbonate foils/films [35][36][37] , formvar coated gold transmission electron microscopy (TEM) grids [38][39][40][41][42] and silicon nitride windows 5,17,[43][44][45][46] , have been used to grow mammalian cells and used for X-ray fluorescence imaging. In comparison among the existing and potential substrates for imaging adherent mammalian cells by XFM, silicon nitride membrane (Si 3 N 4 ) windows are most suitable due to their low fluorescence background and relatively simple elemental composition [4][5][6]47,48 . In addition Si 3 N 4 windows support robust cell attachment and proliferation.…”
Section: Discussionmentioning
confidence: 99%